2003
DOI: 10.3763/cpol.2003.0318
|View full text |Cite
|
Sign up to set email alerts
|

The climatic impacts of land surface change and carbon management, and the implications for climate-change mitigation policy

Abstract: Strategies to mitigate anthropogenic climate change recognize that carbon sequestration in the terrestrial biosphere can reduce the build-up of carbon dioxide in the Earth's atmosphere. However, climate mitigation policies do not generally incorporate the effects of these changes in the land surface on the surface albedo, the fluxes of sensible and latent heat to the atmosphere, and the distribution of energy within the climate system. Changes in these components of the surface energy budget can affect the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(86 citation statements)
references
References 20 publications
1
82
0
3
Order By: Relevance
“…The biological systems responds to a combination of local climatic conditions and land surface conditions (e.g., the amount and spatial configuration of habitat). Managers can identify LULC interventions that modify both local climate conditions and land surfaces conditions that help the biological system achieve conservation goals LULC activities extend the discussion about climate change drivers beyond greenhouse gas emissions and recognize the capacity of LULC activities to ameliorate or exacerbate climate change (Marland et al 2003). The meteorological community provides exhaustive treatments of the physics underlying LULC activities (e.g., Oke 1987), and recent ecological research has convincingly demonstrated its relevance to biological processes.…”
Section: Identifying Biophysical Tools For Climate Adaptationmentioning
confidence: 98%
See 1 more Smart Citation
“…The biological systems responds to a combination of local climatic conditions and land surface conditions (e.g., the amount and spatial configuration of habitat). Managers can identify LULC interventions that modify both local climate conditions and land surfaces conditions that help the biological system achieve conservation goals LULC activities extend the discussion about climate change drivers beyond greenhouse gas emissions and recognize the capacity of LULC activities to ameliorate or exacerbate climate change (Marland et al 2003). The meteorological community provides exhaustive treatments of the physics underlying LULC activities (e.g., Oke 1987), and recent ecological research has convincingly demonstrated its relevance to biological processes.…”
Section: Identifying Biophysical Tools For Climate Adaptationmentioning
confidence: 98%
“…However, these processes play a significant role in determining climate at local, regional, and global scales (Brovkin et al 1999;Kalnay and Cai 2003;Matthews et al 2003;Myhre and Myhre 2003) and, consequently, the effectiveness of climate policy (Marland et al 2003). Recent studies demonstrate that LULC activities have ecologically-important impacts on biophysical conditions such as soil moisture availability (Li et al 2000), length of growing season (White et al 2002), diurnal temperature range (Stone and Weaver 2003;Balling and Cerveny 2003), temperature extremes (Shine et al 2002;Marshall et al 2003), precipitation patterns (Changnon 2003), and severe storm frequency (Rozoff et al 2003) (Table 1).…”
Section: Biophysical Consequences Of Land Use and Land Covermentioning
confidence: 99%
“…Climate change mitigation activities to date, however, have focused almost exclusively on the greenhouse gas consequences of land-use change (Marland et al, 2003). None of the proposed regulations or programs, including the UN Reduced Emissions from Deforestation and Degradation This differentiation in how climate effects of land-use change are treated is also evident in the largest global effort to simulate potential changes in future climate, the Climate Model Intercomparison Project, now in its 5 th incarnation (CMIP5).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose it is necessary to distinguish between CO 2 contributions from oceanic, biospheric and anthropogenic sources and sinks. Monitoring these CO 2 contributions separately is desirable to improve process understanding, to investigate climatic feedbacks on the carbon cycle and also to verify emission reductions and design CO 2 mitigation strategies (Marland et al, 2003;Gurney et al, 2009;Ballantyne et al, 2010).…”
Section: Introductionmentioning
confidence: 99%